A β-FeOOH/MXene sandwich for high-performance anodes in lithium-ion batteries. Issue 27 (19th June 2020) - He, Lu; Tan, Chuan; Sheng, Chuanchao; Chen, Yuanzhao; Yu, Fengjiao; Chen, Yuhui
Abstract : A β-FeOOH/MXene sandwich composite enables improved cyclability and better high-rate performance in lithium-ion batteries. Abstract : FeOOH is one of the earth abundant and high-capacity anode materials for lithium-ion batteries (LIBs), but faces problems of inevitable structure collapse and thus poor capacity retention. Herein, we report a composite of β-FeOOH/Ti3 C2 T x MXene sandwich by an intercalation of β-FeOOH nanorods within single-layer Ti3 C2 T x MXene flakes. After 100 cycles, the β-FeOOH/Ti3 C2 T x composite retains a capacity of 937.5 mA h g −1 at 200 mA g −1, and 671.4 mA h g −1 at 1 A g −1 . The composite as an anode in LIB delivers improved cyclability and better high-rate performance compared to pristine β-FeOOH, which result from the excellent conductivity of single-layer MXene, facilitating mass transport by the sandwich structure. This work provides a strategy for the design of electrodes, particularly in Na-ion and K-ion batteries, which involve active materials that experience volume change and structural damage during cycling.